Effective field theory of anisotropic inflation in Weinberg\'s approach - T Rostami; H Firouzjahi; A Karami (Iranian Journal of Physics Research, 2018)
In this paper, the effective field theory for the anisotropic inflationary universe in Weinberg's approach is studied. We consider the leading correction terms to the standard interactions in the anisotropic inflationary models. These consist of forth derivative of the fields, scalar field, gauge field and metric. Then, the scalar power spectrum is investigated in the presence of higher energy interactions, and the corrections of power spectrum are calculated.